The properties of sputtered copper oxide thin film for sensing application - Low, Jia Wei (2015)
Gas sensor is an important functional device that will guarantee the safety of human from being exposed to hazardous gases. The important features of a gas sensor are the ability to response towards the gas at the shortest time, the sensitivity towards the specific gas and the portability of gas sensor device. In this thesis, the optimum parameters required to deposit CuO thin film for gas sensing application using RF magnetron sputtering was investigated by correlating the copper oxide plasma and thin film. The optimum oxygen flow rate for the deposition of CuO thin film was observed to be 8sccm base on the ratio of copper and oxygen emission obtained from the OES analysis. Moreover, through the XRD analysis it was confirmed that pure CuO compound was formed at above 8sccm oxygen flow rate. As for the substrate bias voltage, the ideal value was -40V base on the ion flux value obtained through Langmuir probe analysis. In addition, comparison on the topography, morphology, roughness and sheet resistance at various substrate bias voltages through FE-SEM, AFM and two-point-probe analysis help confirmed the structure that were suitable for gas sensing application. Besides, the sheet resistance of the CuO thin film that were deposited at -40V substrate bias voltage and 8sccm oxygen flow rate was near to 106Ω which is close to fully oxidized copper oxide thin film. Lastly, a simple experimental setup was constructed to test the functionality of the CuO thin film as a gas sensor.